Wind tunnel investigation of wind load on a ground mounted photovoltaic tracker - Mohapatra, Swagat, author; Bienkiewicz, Bogusz J., advisor; Venayagamoorthy, Subhas K., committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2011)
Wind loading is an important environmental factor to be considered in design of components and support structures of ground mounted photovoltaic tracker systems (PVT). Current understanding of action of wind on such systems is incomplete. Over the past decade, a number of investigations devoted to this topic have been carried out. However, majority of these efforts have been of proprietary nature. As a result, limited amount of data on wind loading on PV systems can be found in open literature. This study describes a wind tunnel study of wind effects on a generic ground mounted photovoltaic tracker system. The study was carried out at the Wind Engineering and Fluids Laboratory, Colorado State University. During the wind tunnel testing, the dynamic wind loading exerted on an isolated PVT system was measured and the effects of various parameters of the system on the wind loading were investigated. The investigated parameters included: the system porosity, inclination angle, wind direction and arrangement of the PV panels. A scaled model of the system was mounted on a High Frequency Force Balance (HFFB) and wind induced forces and moments were measured in a simulated atmospheric boundary layer flow. The work described herein presents an overview of the study and discusses the obtained main findings. It is concluded that certain combination of the system parameters led to a significant reduction in the exerted wind loads. A comparison of wind tunnel based design wind loads with those obtained from American Society of Civil Engineers Standard (ASCE 7-05) demonstrated reasonable agreement between the measured peak wind loads and design loads recommended by the standard.
Keywords: solar energy; wind tunnel; wind engineering; solar tracker